Hubungan Efikasi Diri dengan Pengambilan Keputusan Karir pada Siswa Kelas XII SMK YPM 8 Sidoarjo - Putra, Rachmad Khafid; Affandi, Ghozali Rusyid (Indonesian Journal Publisher, 2024)
This study aims to determine the relationship between self-efficacy and career decision making 12th grade students at Vocational high school YPM 8 Sidoarjo. This type of research use quantitative with a correlational approach. The variables in this study is self-efficacy as the independent variable and career decision making as the dependent variable. The research was conducted at Vocational high school YPM 8 Sidoarjo with a total population of 382 students. The sample in this study were 242 students using the convenience sampling technique. The data collection technique uses a psychological scale, namely the self-efficacy scale and the career decision-making scale, both of which are in the form of a Likert scale. The hypothesis in this study is that there is a positive relationship between self-efficacy and career decision making 12th grade students at Vocational high school YPM 8 Sidoarjo. Data analysis was carried out using the Product Moment correlation technique using the SPSS 25 for windows program. The results of data analysis show a correlation coefficient of 0.300 with a significance of 0.000 <0.05. This indicates that the hypothesis is accepted, which means that there is a relationship between self-efficacy and career decision making. The magnitude of the effect on this variable is 0.300 which is classified as moderate. The limitations of the problems studied in this study are limited to the problem of making career decisions in 12th grade students at Vocational high school YPM 8 Sidoarjo with self-efficacy as a factor to dig deeper information about career decision making.